MULTI DETERMINISTIC BASED ASSESSMENT OF THE BEARING CAPACITY FOR A SHALLOW FOUNDATION: CASE STUDY OF LAGOS SOUTHWEST, NIGERIA - Oladipupo J.T.; Eze U. Stanley; Mohammad K. Ravari; S.H. Waziri; Saleh .A. Saleh; Orji M. Omafume; Avwenaghegha, J.O; Zainab Alaran (Engineering Heritage Journal)
Shallow foundations are a popular and affordable foundation type for construction of buildings and engineering structures. Therefore, precise assessment of the underlying soil structure’s bearing capacity is critical for their successful application. In this study, a multi-deterministic technique has been used to evaluate the bearing capacity of a shallow foundation. Empirical estimation of allowable bearing capacity (BC) was based on data from cone penetration tests employing the Schmertmann’s approach. The BC generally increased with depth across all CPTs, aligning with the observed increase in cone resistance (qc) values. A strengthening soil profile was indicated by the overall rise in the average allowable bearing capacity with depth. The numerical modeling with Plaxis-3Dv24 software application accurately estimated the bearing capacity and settling behavior of the shallow foundation on lateritic clay. The findings are consistent with empirical estimates derived from CPT data, notably for allowable bearing capacity. The average bearing capacity estimated from CPT data was 604.98 KN/m², corresponding to an allowable bearing capacity of 201.66 KN/m². The numerical model predicted an ultimate bearing capacity of 620 KN/m², slightly higher than the empirical estimate, and resulting in an allowable bearing capacity of 206.67 KN/m² with a factor of safety (FoS) of 3 against shear failure. The calculated allowable bearing capacities from both methods are relatively close, indicating a reasonable level of agreement. In terms of settlement, the numerical model predicted initial settlement was 8.0 mm, well within the limiting settlement pressure, while for the empirical data settlement information was available for direct comparison. Therefore, the numerical model provided useful insights regarding settlement. It is critical to recognize that the numerical model’s accuracy is strongly reliant on the input soil parameters (unit weight, Young’s modulus, Poisson’s ratio, cohesion, and friction angle), which were estimated based on field research data and engineering appraisal. Therefore, future research could use advanced constitutive models or laboratory testing to refine these values for more precise numerical simulations. The multi-deterministic technique can be extended to a broader range of case studies involving shallow foundations on lateritic clays, resulting in a more comprehensive database of design variables.